2017
DOI: 10.2105/ajph.2016.303510
|View full text |Cite
|
Sign up to set email alerts
|

Gain in Insurance Coverage and Residual Uninsurance Under the Affordable Care Act: Texas, 2013–2016

Abstract: Many population subgroups have benefited from the ACA's Marketplace, but approximately 3 million Texas residents still lack health coverage. Adopting the ACA's Medicaid expansion is a means to address the lack of coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Competitive advantages of any service enterprise can be obtained by offering the high-quality services to achieve customer’s satisfaction and their patronage decision toward service providers (Hussain, 2016; Wang et al , 2004; Ladhari et al , 2017). Thus, service providers, such as health insurance companies, need to understand the requirement of customer’s need in terms of service quality to provide the maximum satisfaction for their existing and potential customers (Pickett et al , 2017; Saeida Ardakani et al , 2015; Kolstad and Chernew, 2009; Choi et al , 2004; Munnukka et al , 2015). Huang et al (2011) proposed that firm’s service quality has a positive influence on both customers’ satisfaction and their patronage behavioral decision toward the selection of a product or service.…”
Section: Introductionmentioning
confidence: 99%
“…Competitive advantages of any service enterprise can be obtained by offering the high-quality services to achieve customer’s satisfaction and their patronage decision toward service providers (Hussain, 2016; Wang et al , 2004; Ladhari et al , 2017). Thus, service providers, such as health insurance companies, need to understand the requirement of customer’s need in terms of service quality to provide the maximum satisfaction for their existing and potential customers (Pickett et al , 2017; Saeida Ardakani et al , 2015; Kolstad and Chernew, 2009; Choi et al , 2004; Munnukka et al , 2015). Huang et al (2011) proposed that firm’s service quality has a positive influence on both customers’ satisfaction and their patronage behavioral decision toward the selection of a product or service.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, findings of higher likelihoods of uncontrolled diabetes among those enrolled in the ACA plans may be linked to our earlier note that some of the largest groups enrolling in the ACA’s marketplace insurance between 2013 and 2016 were those reporting fair to poor health, Hispanic individuals, individuals aged 50-64 years, and those reporting their highest education as a high school diploma. 16 Thus, it is likely that those enrolled in ACA plans were already facing health inequities, where, for example, past work has identified that individuals with lower education had worse health outcomes and were more likely to die earlier. 31 However, we identified that among those enrolled in the ACA marketplace insurance, that the probability of having non-target A1Cs and separately having uncontrolled A1Cs decreased over time, thereby indicating that those on the ACA marketplace insurance saw gains, even though disparities between those not enrolled persisted.…”
Section: Discussionmentioning
confidence: 99%
“… 15 In terms of health insurance types, there is also evidence that some of the largest groups enrolling in the ACA’s marketplace insurance between 2013 and 2016 were those reporting fair to poor health, Hispanic individuals, individuals aged 50-64 years, and those reporting their highest education as a high school diploma. 16 Furthermore, efforts to identify factors linked to A1C thresholds (i.e., target ranges and controlled levels) are valuable because they can assess a critical, and potentially modifiable aspect of T2D that may be influenced by individual-level, geospatial, and geopolitical factors.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Insurance Regulatory and Development Authority of India (IRDAI) norms, the customer may easily switch or port their existing health insurance policy to another insurance company in the case of perceived poor customer service, claim settlement issues, additional cover facility offered by any other company, and availability of better option or transparency concerns due to the health insurance company reputation (ET 2019 ; IRDAI 2020 ). In mature markets like financial services, customer retention provides a number of intrinsic benefits to the firms (Harrison and Ansell 2002 ; Pickett et al 2017 ). The current study is an initial attempt to examine the role of insurance company reputation, insurance service performance, and positive and negative affect in facilitating customer retention in the health insurance sector and the moderating influence of customer inertia.…”
Section: Introductionmentioning
confidence: 99%